CONSTRUCTION PERFORMANCE ANALYSIS IN THE PROJECT DELIVERY OF TOLL ROAD CONCESSION - Milyardi, Roi; Wirahadikusumah, Reini D.; Abduh, Muhammad; Siregar, Budi H. (Institut Teknologi Bandung, 2020)
AbstractPPP scheme has stimulate increasing the volume of infrastructure development in Indonesia from the period of 2014 and planned until 2025, where the toll road business is carried out by business entities with a concession period. In the PPP scheme, various variables need to be considered, including project cost, project complexity, strong public support, and performance indicators in each phase of toll road concession. The construction phase in the PPP scheme in Indonesia is the responsibility of the business entity regulated in PP No. 43 of 2013. Determination of project delivery on toll road construction projects is a strategy of the business entity to control the performance of the toll road construction project it manages. In the complexity of the variables in PPP, a variable pattern with project delivery is needed to find an effective strategy in achieving good construction performance. The purpose of this study is to identify patterns of achievement of construction performance on variations in project delivery in the toll road PPP scheme. The analytical approach QCA (Qualitative Comparative Analysis) is taken, with 14 BUJT case studies in 4 toll road networks in Indonesia. From the results of the study, two project deliveries, design-bid-build and design & build, were identified, which identified that project delivery variations did not have a strong influence on the performance of toll road construction projects, where other toll road PPP concession, such as business scheme, project management maturity, construction cost, length of road, corporation relation between business entities and contractor contractor's financial scheme, and land acquisition scheme variables which is more powerful. AbstrakMeningkatnya volume pembangunan infrastruktur di Indonesia pada periode 2014 dan direncanakan hingga tahun 2025 didorong dengan skema KPBU, dimana pengusahaan jalan tol dilakukan badan usaha dengan timbal balik suatu masa konsesi. Dalam skema KPBU, berbagai variabel perlu diperhatikan, diantaranya biaya proyek, kompleksitas proyek, dukungan publik yang kuat, hingga indikator kinerja pada setiap fase pengusahaan jalan tol. Fase konstruksi pada skema KPBU di Indonesia, menjadi tanggung jawab badan usaha yang diatur dalam PP No.43 Tahun 2013. Penentuan project delivery pada proyek konstruksi jalan tol menjadi strategi badan usaha mengendalikan kinerja proyek kosntruksi jalan tol yang dikelolanya. Dengan kompleksitas variabel dalam KPBU, diperlukan pola variabel dengan project delivery agar ditemukan strategi yang efektif dalam mencapai kinerja konstruksi yang baik. Tujuan dari penelitian ini adalah mengidentifikasi pola capaian kinerja konstruksi pada variasi project delivery di skema KPBU jalan tol. Pendekatan analisis yang dilakukan adalah QCA (Qualitative Comparative Analysis), dengan 14 studi kasus BUJT di 4 jaringan jalan tol di Indonesia. Dari hasil penelitian, diidentifikasi bahwa variasi project delivery tidak berpengaruh secara kuat terhadap capaian kinerja proyek konstruksi jalan tol. Kinerja konstruksi jalan tol lebih kuat dipengaruhi oleh variabel-variabel pengusahaan KPBU jalan tol lainnya, yaitu skema pengusahaan, maturitas manajemen proyek, biaya konstruksi, panjang jalan, skema finansial kontraktor, hubungan korporasi BUJT-korporasi, dan skema pengadaan tanah.